The effects of high-heeled shoes on gait parameters in healthy adult women - Kyoma Tanigawa; Hiroki Shimizu; Anuradhi Bandara; Misa Toyota; Shota Suzuki; Momoko Nagai-Tanima; Tomoki Aoyama (PLoS ONE, 2025)
Background Walking is essential in daily life, and footwear type significantly affects walking patterns. High-heeled shoes increase the risk of knee osteoarthritis and falls in women. Traditional studies often use treadmills or unfamiliar footwear, which may not reflect daily walking. This study investigated the impact of high-heeled shoes on walking parameters in healthy adult women using in-shoe motion sensors. Methods Seventeen healthy adult women without pain during walking participated. They walked for 6 minutes along a 30-meter corridor wearing high-heeled shoes and sneakers. Walking data were recorded using an in-shoe motion sensor system every 2 minutes. The average of three valid consecutive steps was calculated automatically. Statistical analysis compared the mean walking parameters between the high-heel and sneaker groups. Results The high-heel group showed significantly reduced foot clearance, stride length, peak plantar angle in dorsiflexion, and peak plantar angle in plantarflexion, and significantly greater toe-out angle in spatial parameters. Spatiotemporal parameters revealed significantly reduced walking speed and maximum swing phase speed in the high-heel group. No significant differences were observed in temporal parameters between the groups. Conclusions Since this study collected gait data under conditions similar to daily life, it provides data suitable for practical applications and may contribute to future research evaluating everyday gait. Additionally, future studies should include a broader range of participants and incorporate measurement devices capable of capturing hip and knee joint movements, providing a more comprehensive evaluation of the effects of high-heeled shoes on gait in healthy adult women.